Preparation, Modification, and Characterization of Alginate Hydrogel with Nano-/Microfibers: A New Perspective for Tissue Engineering. (5th June 2013) - Palma Santana, Bianca; Nedel, Fernanda; Piva, Evandro; Varella de Carvalho, Rodrigo; Fernando Demarco, Flávio; Lenin Villarreal Carreño, Neftali
Abstract : We aimed to develop an alginate hydrogel (AH) modified with nano-/microfibers of titanium dioxide (nfTD) and hydroxyapatite (nfHY) and evaluated its biological and chemical properties. Nano-/microfibers of nfTD and nfHY were combined with AH, and its chemical properties were evaluated by FTIR spectroscopy, X-ray diffraction, energy dispersive X-Ray analysis, and the cytocompatibility by the WST-1 assay. The results demonstrate that the association of nfTD and nfHY nano-/microfibers to AH did not modified the chemical characteristics of the scaffold and that the association was not cytotoxic. In the first 3 h of culture with NIH/3T3 cells nfHY AH scaffolds showed a slight increase in cell viability when compared to AH alone or associated with nfTD. However, an increase in cell viability was observed in 24 h when nfTD was associated with AH scaffold. In conclusion our study demonstrates that the combination of nfHY and nfTD nano-/microfibers in AH scaffold maintains the chemical characteristics of alginate and that this association is cytocompatible. Additionally the combination of nfHY with AH favored cell viability in a short term, and the addition of nfTD increased cell viability in a long term.